Factors causing Low Achievement in Theology Students at Theological College in Semarang, Indonesia - DIANA, Ruat; MARDIHARTO, Mardiharto; SIDABUTAR , Monang (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Education is an endeavour to advance human life. There are times in educational processes where students have low achievement. At Simpson Theological Seminary, there are thirteen low-achieving students within Class 2019. Since learning achievement reflects learning process accomplishment, a review is needed to find factors underlying low achievement. In order to find these factors, a qualitative phenomenological approach was used in conducting the research, which in the process employed thirteen low-achieving students as informants. The collected data were analysed using Miles and Huberman model analysis with three stages: data reduction with coding, presentation of the data from the coding to find the similarity of words, and conclusion or verification. The research shows that internal and external factors intertwine, creating a significant impact and causing low achievement. The dominant internal factor that, based on data percentage coverage, caused low achievement is psychological in nature: students from outside Java had adaptation difficulties. Some external factors also contributed to causing this condition, such as the lack of learning tools in the form of learning media and books in the library, the parents’ less-than-affluent economic condition, which triggered the low purchasing power of students towards learning support facilities, and the crowded and noisy dormitory, which made it difficult for students to concentrate when studying.